Liposome as Mucosal Vaccine Drug Delivery System - Kuni Zuaimah Barikah (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2022)
Vaccines are a pharmaceutical product that is used to overcome infectious diseases and are a new therapeutic strategy for chronic disease treatment, recently.  However, the parenteral route as the main route of vaccination nowadays has several limitations, so mucosal vaccines rise as a potential alternative for vaccine delivery. A few research found that mucosal vaccines have better immune protection against pathogens.  Liposome, a biodegradable particulate drug delivery system, offers the most promising future as a mucosal vaccine delivery system because of its versatility. A liposome can act as an adjuvant by direct stimulation of immune response in several ways. Several liposome properties that affect system uptake after mucosal administration are size, surface charge, and hydrophilicity. To enhance liposome ability as mucosal vaccine, targeted liposomes, such as mannose receptor-targeted liposome, macrophage galactose-type C-type lectins (MGL) targeted liposome, DC-specific intracellular adhesion molecule-3 grabbing non-integrin (DC-SIGN), and M cells targeted liposome then developed.